PENGARUH REGULASI DIRI (SELF REGULATION) DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR BIOLOGI PADA PESERTA DIDIK KELAS XI MIA MAN 1 BULUKUMBA - Reski Hastuti; Ulfiani Rahman; Muchlisah Muchlisah (Al-AHYA: Jurnal Pendidikan Biologi, 2019)
This study aims to (1) describe the self regulation of students of class XI MIA MAN 1 Bulukumba, (2) describe the learning motivation of students in class XI MIA MAN 1 Bulukumba, (3) describe the biology learning outcomes of students XI MIA MAN 1 Bulukumba, (4) the effect of self regulation on learning biology of students of class XI MIA MAN 1 Bulukumba, (5) the influence of learning motivation on learning biology of students in class XI MIA MAN 1 Bulukumba and (6 ) the influence of self regulation and learning motivation of students in class XI MIA MAN 1 Bulukumba,on learning biology outcomes. This study included quantitative research with ex post facto correlation methods. This research is a population study so that the subject of this study is all 71 students of class XI MIA MAN 1 Bulukumba. This study used self regulation and learning motivation scale instrument and also documentation. Data were analyzed with descriptive and inferential statistics. The results of this study are (1) students self regulation is in the medium category. (2) Learning motivation is in the medium category. (3) Learning outcomes is in high category. (4) Self regulation has a positive and significant influence on learning biology outcomes (5) Learning motivation has a positive and significant influence on learning biology outcomes. (6) Self regulation and learning motivation have positive and significant influence on the results learning biology outcomes. It can be suggested from this research, that teachers can use this as an input to redesigning the Lesson plan in order to improve self regulation and learning motivation of the students.Key words: Self Regulation, Motivation Learning, Learning Outcomes Biology.